Tree Diversity and Population Structure in a Lowland Tropical Rainforest in the Eastern Himalayas, India - Deb, Panna; Sundriyal, R. C.; Shankar, Uma (Indian Forester, 2009)
The tropical rainforests in North-East India are the least investigated despite their high diversity and being located at the northern-most limit of the rainforests that occur farthest from the equator. The lowland tropical rainforests at Namdapha National Park, Arunachal Pradesh (Eastern Himalayas) were investigated for tree species diversity, population structure and species richness with reference to three distinct canopy covers, viz. an Altingia-mixed species stand, Shorea-Dipterocarp stand, and an Albizia stand. A total of 1,053 trees covering 130 species in 44 families were recorded at â‰¥10 cm dbh, while 34,526 individuals covering 104 species in 44 families were enumerated at <10 cm dbh. The tree species richness for three inventoried stands varied from 98, 54 and 20 species in â‰¥10 cm dbh with overall density of 418, 390 and 245 trees ha-1 for the three stands respectively. Lauraceae, Dipterocarpaceae, Euphorbiaceae, Fagaceae and Leguminosae dominated the flora; thus the forest exhibited typical attributes of lowland evergreen tropical rainforests.